Which determinants are considered to be important for adherence to Negative Pressure Wound Therapy: A multimethods study. Issue 2 (May 2021) - Janssen, Alexandra H.J.; Wegdam, Johannes A.; de Vries Reilingh, Tammo S.; Vermeulen, Hester; Eskes, Anne M.
Abstract: Aim: To explore the extent of patients that choose to cease Negative Pressure Wound Therapy (NPWT) prematurely in a clinical setting, and to explore the determinants of nonadherence. Method: This study exists out of: (1) a retrospective study to assess the number of patients who ceased NPWT prematurely; (2) a narrative review (NR) to identify determinants of nonadherence; and (3) a survey among wound care specialists to explore specific determinants of nonadherence to NPWT. Results: (1) Based on the retrospective study, 20% ceased NPWT prematurely because of experienced limitations in daily activities. (2) Based on 22 studies, 23 determinants that might influence nonadherence were identified and added as questions in the survey. (3) Twenty-two percent (n = 136) wound care specialists completed the survey. Confidence with the healthcare team, consistency in therapy advices, coping with pain, former negative experiences with NPWT, a normal activity pattern, social support from family or friends, and support from the healthcare team were identified as highly relevant determinants of nonadherence to NPWT. Only religion scored distinctively lower. Conclusion: This study is a first step in exploring the determinants of nonadherence to NPWT. In 20% NPWT was prematurely ceased at the request of the patient, this means that this therapy may have not been the best choice of therapy for this particular patient. The identification of potential determinants of nonadherence may help healthcare professionals in their dialogue with patients. The next step should be a prognostic study to assess which determinants best predict adherence to NPWT. Highlights: A significant amout of patients premature terminate NPWT due to experiences restrictions in daily life. The decision of wound treatment should be made in a shared decision way. The identification of potential determinants of nonadherence may help healthcare professionals in their dialogue with patients.